Indigenous Knowledge on Pest Management in Rice Production in the Province of Masbate - Dollison, Mohammad D.; Dollison, Beverly B. (Future Science / FSH-PH Publications, 2023)
A total of 90 rice farmers who are used in adopting IK in rice pest management were considered using a convenient sampling method in selecting respondents. The data were subjected to descriptive statistics. The result showed that 40% of rice farmers are 51-60 years old, male (80%), married (95%), elementary graduate (44%), with a household size of 1 to 5 members (70%), and 37% were engaged in farming for 5 to 10 years. Furthermore, farmers are dominated by the land owner (57%), planted traditional or local varieties (61%), with farm size of less than 1 hectare (47%), and obtained an average yield of 50 caravans per hectare (35%). Rice farmers claimed that IK was handed down by their ancestors with less intervention from agricultural institutions, and rice farmers have practiced it for 20 to 30 years. Most (32%) farmers perceived they were more familiar with indigenous knowledge than new technology. The level of awareness of IK on pest management in rice production in the province of Masbate revealed that rice farmers were aware of the IK practices with a weighted mean of 2.87. Furthermore, data also revealed that the level of utilization of rice farmers who utilized IK on pest management in rice production is often with a general weighted mean of 2.85. Similarly, the result shows that the IK practices on pest management in rice production in the province of Masbate are cost-effective, with a general weighted mean of 2.85.